2017
DOI: 10.1089/scd.2016.0226
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Proliferation and Differentiation of Human-Induced Pluripotent Stem Cell-Derived Cardiac Progenitor Cells Depend on Bone Morphogenetic Protein Signaling Regulation by GREMLIN 2

Abstract: Heart development depends on coordinated proliferation and differentiation of cardiac progenitor cells (CPCs), but how the two processes are synchronized is not well understood. Here, we show that the secreted Bone Morphogenetic Protein (BMP) antagonist GREMLIN 2 (GREM2) is induced in CPCs shortly after cardiac mesoderm specification during differentiation of human pluripotent stem cells. GREM2 expression follows cardiac lineage differentiation independently of the differentiation method used, or the origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…In addition, the overexpression of interleukin (IL)-33 could potentially result in the acceleration of platinum-induced apoptosis and prohibit the invasion of GC cells through the suppression of the JNK signaling pathway, as indicated by a previously conducted study [17]. Another study demonstrated that GEM2 could lead to the inhibition of canonical BMP signaling, which then accelerated the proliferation of cardiac progenitor cells through the indirect induction of differentiation via the JNK signaling pathway [18]. In the present study, we investigate the role and underlying mechanism of GREM2 in GC development with the objective of providing a new and effective therapeutic strategy for GC.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the overexpression of interleukin (IL)-33 could potentially result in the acceleration of platinum-induced apoptosis and prohibit the invasion of GC cells through the suppression of the JNK signaling pathway, as indicated by a previously conducted study [17]. Another study demonstrated that GEM2 could lead to the inhibition of canonical BMP signaling, which then accelerated the proliferation of cardiac progenitor cells through the indirect induction of differentiation via the JNK signaling pathway [18]. In the present study, we investigate the role and underlying mechanism of GREM2 in GC development with the objective of providing a new and effective therapeutic strategy for GC.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have demonstrated that gremlin exerts its biological effects by activating TGF-β/ Smad, AKT, ERK and other signaling pathways [16,31]. Our previous studies demonstrated that gremlin could dose-dependently activate the Smad2/3 signaling pathway.…”
Section: The Roles Of Akt Erk and Smad2/3 Signaling Pathways In The mentioning
confidence: 91%
“…Among them, Nkx2.5 and Gata4 were tightly associated with cardiogenic differentiation [38]. Gli2 [39], Grem2 [40], E2f7 [41], Nr2f2 [42] and Shox2 [43] are also related to stem cell biology. Interestingly, SETD4 KO significantly changed the transcript of these genes.…”
Section: Discussionmentioning
confidence: 99%